La loi du 3 janvier 1979 et la communication des documents - Charpy, Jacques (Gazette des archives, 1979)
The Archive Law of 3 January 1979 and access to archives. Access to information is nowadays considered to be a fundamental right of the citizen. The author explains the former state of regulations in this field before explaining the new one. Access to administrative documents will need the elaboration of technical solutions and a co-ordination between Archives and administrations from which the documents come. Dérogations to the general rules of access will have to be organised, as well as reading-room regulations and delivery of copies.

La loi du 3 janvier 1979 (France) et la communication des documents - Charpy, Jacques (La Gazette des archives, 1979)

La loi du 17 juillet 1978 (France) : de la liberté d'accès aux documents administratifs - Gorgeon-Demartres, A. (La Gazette des archives, 1979)

Les recherches, communications et délivrances de copies - Blaquière, Henri (Manuel d'archivistique. Théorie et pratique des Archives publiques en France, 1970)